Assoc. Prof. Dr. Doğan Köse Oxidative Stress and DNA Damage Profile in Cord Blood of Vitamin B₁₂-Deficient Newborns : B₁₂ Deficiency, Oxidative Stress and Neonatal DNA Damage - Köse, Doğan; Demir, Mahmut; Kirmit, Adnan (Journal of Medical Biochemistry, 2025)
Background: Vitamin B₁₂ is an essential micronutrient that plays a critical role in DNA synthesis, methylation, and cellular energy metabolism. Its deficiency during the intrauterine period has been associated with increased oxidative stress and DNA damage, which may have lasting effects on the newborn. 8-hydroxy-2’-deoxyguanosine, a biomarker of oxidative DNA damage, is widely used to evaluate these processes. However, the effects of vitamin B₁₂ deficiency on such biomarkers at birth remain insufficiently investigated. Methods: This single-center, prospective case-control study included 48 term newborns with vitamin B₁₂ deficiency and 40 healthy controls matched for gestational age. Vitamin B₁₂, total oxidant status, total antioxidant status, oxidative stress index, and 8-hydroxy-2’-deoxyguanosine were measured from umbilical cord venous blood obtained immediately after delivery. Oxidant and antioxidant levels were determined using colorimetric methods, and oxidative DNA damage was assessed by enzyme-linked immunosorbent assay. Group comparisons were made using appropriate statistical tests, with significance set at p<0.05. Results: Vitamin B₁₂ levels were significantly lower in the patient group. Levels of 8-hydroxy-2’-deoxyguanosine, total oxidant status, and oxidative stress index were significantly higher, whereas total antioxidant status showed no significant difference between groups. Conclusions: Term newborns with vitamin B₁₂ deficiency exhibited increased oxidative stress and measurable oxidative DNA damage at birth. The unchanged total antioxidant status may reflect the immature antioxidant defense system in the neonatal period. Biomarker evaluation at delivery could assist in early identification and intervention for infants at risk of complications associated with intrauterine vitamin B₁₂ deficiency.